Surgical management of peritonitis secondary to acute superior mesenteric artery occlusion - Acosta, Stefan (Baishideng Publishing Group Inc, 2014)
Diagnosis of acute arterial mesenteric ischemia in the early stages is now possible using modern computed tomography with intravenous contrast enhancement and imaging in the arterial and/or portal phase. Most patients have acute superior mesenteric artery (SMA) occlusion, and a large proportion of these patients will develop peritonitis prior to mesenteric revascularization, and explorative laparotomy will therefore be necessary to evaluate the extent and severity of intestinal ischemia, and to perform bowel resections. The establishment of a hybrid operating room in vascular units in hospitals is most important to be able to perform successful intestinal revascularization. This review outlines current frontline surgical strategies to improve survival and minimize bowel morbidity in patients with peritonitis secondary to acute SMA occlusion. Explorative laparotomy needs to be performed first. Curative treatment is based upon intestinal revascularization followed by bowel resection. If no vascular imaging has been carried out, SMA angiography is performed. In case of embolic occlusion of the SMA, open embolectomy is performed followed by angiography. In case of thrombotic occlusion, the occlusive lesion can be recanalized retrograde from an exposed SMA, the guidewire snared from either the femoral or brachial artery, and stented with standard devices from these access sites. Bowel resections and sometimes gall bladder removal due to transmural infarctions are performed at initial laparotomy, leaving definitive bowel reconstructions to a planned second look laparotomy, according to the principles of damage control surgery. Patients with peritonitis secondary to acute SMA occlusion should be managed by both the general and vascular surgeon, and a hybrid revascularization approach is of utmost importance to improve outcomes.